La enseñanza de la Arqueología y sus maestros en la Escuela Superior de Diplomática - Maier Allende, Jorge (Revista General de Información y Documentación, 2009)
The Escuela Superior de Diplomática, founded on 1856 by the aid of the Real Academia de la Historia, was the first university official centre in Spain where Archaeology was ever tougth. Nevertheless, public academic teaching of Archaeology first started at the end of the Fernando VII Reign and the beginning of María Cristina de Borbón Regency. Universitary Archaeology teaching at the Escuela was mostly museographic and emphathized about Archaeology of Art. From a primigenious chair, there will be three new ones to grow up independent. These chairs included the three main ways of Antiquity Science: Numismatic and Epigraphy, Ancient Geography and Archaeology of Art. These chairs were occupied by professors with different qualities.